Cognitive and Emotional Biases in Investment Decisions: An Analysis of Muslim Investor Behavior in the Sharia Stock Market - Rani Febriyanni; Andri Soemitra; Isnaini Harahap (Sharia Economic and Management Business Journal (SEMBJ), 2025)
Background: This study investigates the influence of cognitive and emotional biases on investment decisions in the Indonesian Sharia stock market. Method: Using a mixed-method approach with a sequential explanatory strategy, quantitative data were analyzed with Structural Equation Modeling-Partial Least Squares (SEM-PLS), followed by qualitative insights through interviews, observations, and documentation. Results: The findings reveal that emotional bias indirectly affects investment decisions through investor behavior, while cognitive bias also shows a significant influence. Investor behavior plays a crucial mediating role, reflecting how biases are translated into real investment actions. Sharia-based investors tend to be more cautious and guided by religious values, which function as a filter in decision-making, yet they remain vulnerable to emotional factors such as overreaction and herd behavior. Institutional investors appear more systematic in managing biases compared to individual investors, who are more easily influenced by emotions. The study highlights the importance of behavioral factors in shaping investment decisions in Sharia markets, suggesting that financial literacy, investor education, and long-term strategies are essential to minimize the negative effects of cognitive and emotional biases. Conclusion: These findings contribute to understanding investor psychology in Islamic finance and provide insights for regulators and practitioners to strengthen market stability.